LANGUAGE STYLE AND MOTIVATION AMONG TEENAGERS IN WESTERN AND NORTHERN SURABAYA: A COMPARATIVE CASE STUDY - Cicilia Deandra Maya Putri; Fariq Shiddiq Tasaufy; Ayunita Leliana; Slamet Setiawan (University of Kuningan, 2025)
The ever-increasing use of English as a foreign language in Indonesia calls for differing language styles performed by various communities. Furthermore, English users are motivated to learn the language for many reasons. As the second-largest city in Indonesia, Surabaya is home to a diverse range of ethnicities, making it an interesting place to investigate further. Shifts in expression and tendencies in the use of English can be observed in language enclaves in Surabaya, particularly in the North Surabaya (NS) and West Surabaya (WS) areas. The north is predominantly inhabited by Arab-Madurese ethnicities, whereas the west is inhabited by Chinese. The present study aims to identify and compare the English language styles used by teenagers of NS and WS as well as the motivation underlying their English proficiency. Using qualitative approaches, incorporating interviews with four informants aged 13-19, the findings revealed differences in the language style used by these communities, specifically in phonological and grammatical features. Furthermore, learning a language is facilitated by various forms of motivation, including instrumental, integrative, extrinsic, and intrinsic motivation. Language learners' motivation may vary over time, and different motivational styles can interact with one another (Dörnyei, 1998; Brown, 2000). By fostering a more diverse and flexible learning environment, the result promotes an effective method to grow students' language proficiency. The study contributes to the advancement of sociolinguistics and provides insight into regional linguistic variations.